2022
DOI: 10.1038/s41598-022-22133-z
|View full text |Cite
|
Sign up to set email alerts
|

Tactile facilitation during actual and mere expectation of object reception

Abstract: During reaching and grasping movements tactile processing is typically suppressed. However, during a reception or catching task, the object can still be acquired but without suppressive processes related to movement execution. Rather, tactile information may be facilitated as the object approaches in anticipation of object contact and the utilization of tactile feedback. Therefore, the current study investigated tactile processing during a reception task. Participants sat with their upper limb still as an obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, once the hand starts moving, any visual memory should be eliminated, or substantially reduced. If the vibration, or other tactile information, was informative to the movement task, participants might have detected more vibrations as task difficulty increased, similar to Voudouris & Fiehler [ 5 ] where task-relevant vibrations were enhanced and task-irrelevant ones were suppressed [ 5 ] or similar to Manzone, Tremblay and Chua [ 59 ] who found that the expectation of intercepting a real world object led to lower detection thresholds [ 59 ].…”
Section: Discussionmentioning
confidence: 90%
“…However, once the hand starts moving, any visual memory should be eliminated, or substantially reduced. If the vibration, or other tactile information, was informative to the movement task, participants might have detected more vibrations as task difficulty increased, similar to Voudouris & Fiehler [ 5 ] where task-relevant vibrations were enhanced and task-irrelevant ones were suppressed [ 5 ] or similar to Manzone, Tremblay and Chua [ 59 ] who found that the expectation of intercepting a real world object led to lower detection thresholds [ 59 ].…”
Section: Discussionmentioning
confidence: 90%